PAI Teacher's Strategy in Building a Classroom Environment That is Friendly to Children with Special Needs - Fadhluzzakiyy, Kemas Ahmad; Sania, Fitri; Kalsum, Umi; Oviyanti, Fitri; Maryamah, Maryamah (FKIP - Universitas Riau, 2025)
Effective classroom learning depends on implementing appropriate strategies and creating a supportive environment, especially for students with disabilities. This study explores the strategies adopted by Islamic Religious Education (PAI) teachers at Az-Zahrah Islamic Elementary School Palembang to establish a friendly classroom environment for children with special needs. The research focuses on seven students with neurodevelopmental disorders who face challenges in communication, social interaction, and exhibit tantrums. Using a descriptive qualitative research design, data were collected through observation, interviews, and document analysis, with the PAI teacher as the main subject. The findings reveal that effective strategies include understanding and addressing individual needs, fostering an inclusive learning atmosphere, customizing teaching methods for special needs students, and applying clear and straightforward communication. However, significant challenges, such as managing classroom dynamics and ensuring harmonious interactions among peers, often demand additional time and effort. This study highlights the critical role of PAI teachers in overcoming these challenges and creating an inclusive, supportive educational environment that accommodates all students, particularly those with special needs. These findings underscore the need for continuous professional development for teachers in inclusive education practices.